THE ROLE OF GOVERNMENT IN EMPOWERING UMKM: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The role of government in MSME empowerment is the actions and policies taken by public authorities to support the development and sustainability of Micro, Small, and Medium Enterprises. This includes providing access to capital, fiscal incentives, supportive regulations, infrastructure development, as well as training and business support programmes, with the aim of increasing the competitiveness and contribution of MSMEs to the national economy. The study in this research uses the literature method. The results show that the government serves as the main facilitator in creating an enabling environment for MSME growth through appropriate fiscal and regulatory policies. This includes providing access to capital, fiscal incentives, and simpler regulations, as well as developing physical and digital infrastructure. In addition, the government also plays a role in improving the capacity and competence of MSME businesses through training programmes, business consultations, and market access facilitation. In conclusion, with active support and synergy from the government and related stakeholders, an ecosystem that supports the development of MSMEs can be created, which in turn encourages national economic growth and community welfare.